Herd Improvement and Management - Gaur, G. K.; Patel, B. H.M.; Singh, Mukesh; Dutt, Triveni (Indian Farming, 2015)
The Livestock Production and Management Section at IVRI wasestablished with the merging of Livestock Production Research,Swine Production Farm and the Sheep and Goat Farms. The Sectionhas been conducting research on production and management aspects of various livestock species. Now the emphasis is also being given to research on elite male/female selection program, DNA selection, sustaining production under climate change, housing, feeding and health care, etc.